2016
DOI: 10.1007/jhep02(2016)180
|View full text |Cite
|
Sign up to set email alerts
|

Width of the flux tube in compact U(1) gauge theory in three dimensions

Abstract: We study the squared width and the profile of flux tubes in compact U(1) lattice gauge theory in three spacetime dimensions. The results obtained from numerical calculations in the dual formulation of this confining theory are compared with predictions from an effective bosonic-string model and from the dual-superconductor model: it is found that the former fails at describing the quantitative features of the flux tube, while the latter is in good agreement with Monte Carlo data. The analytical interpretation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 110 publications
5
28
0
Order By: Relevance
“…We will try to find some numerical evidence for this. We remark that the glueball masses we will obtain in this Section are consistent with those obtained in [8,12,13] but with much smaller errors. Our string tensions on the other hand, while also being consistent with the values in [12,13], are considerably less precise than the latter, because of the very different techniques employed.…”
Section: Glueballs and String Tensionsupporting
confidence: 88%
See 3 more Smart Citations
“…We will try to find some numerical evidence for this. We remark that the glueball masses we will obtain in this Section are consistent with those obtained in [8,12,13] but with much smaller errors. Our string tensions on the other hand, while also being consistent with the values in [12,13], are considerably less precise than the latter, because of the very different techniques employed.…”
Section: Glueballs and String Tensionsupporting
confidence: 88%
“…We remark that the glueball masses we will obtain in this Section are consistent with those obtained in [8,12,13] but with much smaller errors. Our string tensions on the other hand, while also being consistent with the values in [12,13], are considerably less precise than the latter, because of the very different techniques employed. However our calculations are useful and complementary both because they are for closed flux tubes rather than the open flux tubes of [12,13], and also, more importantly, because we are able to calculate the energies of excited flux tubes, as we will do in Section 5.…”
Section: Glueballs and String Tensionsupporting
confidence: 88%
See 2 more Smart Citations
“…Following an analogous study for the Ising model [147], in ref. [106] it was shown that the profile of the flux tube in compact U(1) gauge theory at zero temperature has an exponential profile: this is what one expects, if the vacuum of the theory is interpreted as a dual superconductor [134][135][136]. In addition, we also consider the two-point correlation function…”
Section: )mentioning
confidence: 81%